Maqashid Syariah Perspective on Legal Protection of Children in Narcotics Violation Cases - Marsaid (International Journal of Advanced Science and Technology, 2020)
Children are the nation’s next generation that needs to be guaranteed each of their rights. Ironically lately the fact that drug users are actually done more by teenagers and young people, a potential age for development. Children as narcotics abusers are only victims. So that it is not right, the state gives the punishment by looking at the same between the child abuser with the real adult criminal (dealer). Based on that reality, there are several things that become the main points in the discussion of this article, namely, First, how is the paradigm of Maqashid Shariah on the protection of child victims of narcotics abusers? Second, how is the legal protection of children as victims of narcotics abusers? Based on this study, it can be concluded that first, the goal of punishment in Islam is in the form of Recovery / Repair (al-Islah) and Restoration (al-Isti’adah) by means of rehabilitation of narcotics abusers children as a manifestation of Maqashid Shariah to safeguard the proposal of al-khamsah above which at least in this case to choose the future of a child’s life and maintain a sense of dependence on narcotics. Secondly, legal protection for children who use narcotics since the enactment of Law number 11 of 2012 concerning child protection places more emphasis on the process of handling in diversion with a restorative justice orientation. During this time the rehabilitation process at the rehabilitation center has been going quite well but there are some obstacles encountered, such as human resources in the field of law enforcement that have not worked with the restoration paradigm, and the lack of facilities in remote areas for rehabilitation. Therefore, to make rehabilitation effective for children who use narcotics will be greatly influenced by the child’s internal factors and external factors that must always support the child victims of narcotics abusers.